Pattern Design of Ethnic Clothing Based on Stretchable Nanofiber Fabrics - Xueqing Lu; Jing Wen; Xiaohua Shao (Advances in Materials Science and Engineering)
With the rapid development of social economy, people’s material and spiritual living standards have been greatly improved, and the demand for clothing has also increased. Chinese clothing has distinct national characteristics, and it contains rich national culture. Through a lot of research, it will be found that most of the national costume patterns represent some symbols with specific meanings. From the symbols, we can see the status, hobbies, and beliefs of the costume owners. At present, the popularity of traditional ethnic clothing is low, for which stretchable nanofiber fabrics are introduced in this paper. Through the influence of image rotation, scale change, noise interference, and other factors, a method for extracting features of ethnic clothing patterns based on image rotation, scale change, and noise interference is proposed. It uses digital inkjet printing to design patterns on nanofiber fabrics, compares the satisfaction degree of the nanofiber fabric national costumes designed in this paper and traditional national costumes, and divides the satisfaction into four levels: satisfied, relatively satisfied, general, and dissatisfied. The experimental results showed that the satisfaction rate of the ethnic costumes designed in this paper has reached 79.12%, which has been greatly improved compared with the traditional ethnic costumes.